(untitled) (Research, Society and Development, 2020)
The SRTM synthetic aperture interferometric radar data have great potential for studies involving altimetry, since, in addition to being freely available on the internet, they are also geocoded, facilitating their treatment in Geographic Information System. However, the SRTM data has some usage limitations, including the Canopy Effect, a consequence of the model considering the top of the vegetation as a relief feature. Another limitation, no less important, especially for the use of these data in flat areas, refers to the vertical precision of these data, since in the area of this study, located in the Pantanal, a difference of only one meter has an important significance. The present work aims to evaluate the altimetry data from SRTM, TOPODATA and GLS data; to analyze the vertical accuracy, by comparing the data of these sensors with the altitude data of the geodesic landmarks of the Brazilian Institute of Geography and Statistics; and apply Moving Average Low Pass Filter to correct the "Canopy Effect" of SRTM data. The study area chosen to carry out all these analyzes is included between the Pantanais do Negro and Nhecolância. The applied methodology was developed in a free platform GIS environment: GRASS-GIS, Quantum GIS and SPRING. The SRTM data used allowed us to assess the altimetric difference between the Pantanal do Negro and Nhecolândia. Filters applied to SRTM data substantially reduced the main features associated with the canopy effect of vegetation.